Geographical Information Systems and Multicriteria Decisions Integration Approach for Hospital Location Selection - Eldemir, Fahrettin; Onden, Ismail (WORLD SCIENTIFIC PUBL CO PTE LTD, 2016)
While establishing a new health facility, such as hospitals, multiple factors should be taken into consideration. Due to the variety, the impacts of these factors on location decision should be evaluated initially. Then, spatial effects of the location factors on the plane should be determined to reach an acceptable decision. These factors can be clustered under the main criteria that are competition, accessibility and environment. Attributable to the problem structure, the decision criteria can be represented with a hierarchical way, and evaluations of the priorities of the decision criteria can be done with the Analytic Hierarchy Process technique. On the other hand, spatial convenient levels of the decision criteria and suitability map can be created with GIS/spatial analysis. Integration of these two different approaches is proposed for locating a new hospital facility. By the integration methodology proposed here, a novel approach for a hospital location decision is brought to the literature. To test the integration process, 13 criteria are determined as decision criteria. Anatolia Region of Istanbul, Turkey is selected as the study area due to the high health care demand in that region. The alternative nodes are found with soil formation considerations. The nodes represented the convenient construction sites for the new facility. After reaching the ideal solution, a sensitivity analysis is conducted on AHP-GIS integration for measuring the effectiveness of the alternative scenarios. After completion of the study, it has been observed that the methodology is capable of measuring the land suitability levels and works with all factors without having any problem.
Keywords: Multi-criteria evaluation; geographic information systems; hospital location selection; multi-criteria spatial decision making; ANALYTIC HIERARCHY PROCESS; LANDFILL SITE SELECTION; SUPPORT-SYSTEM; FUZZY AHP; GIS; FACILITY; REGION; MCDM; MODEL; Computer Science; Operations Research & Management Science